PERANCANGAN SISTEM INFORMASI BERBASIS WEB UNTUK PROSES PENGELOLAAN PAKAN PADA CV SEHATI FARM - Evangelyn Yovita; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Recently, technology developments have had a great impact on the company's business processes. To support the company's business processes, a web-based information system was created for the feed management process. The application creation method uses the agile method, where there are several stages that will be passed, namely planning, analysis, design, implementation, and maintenance. The system development process uses UML (Unified Modeling Language). For the creation of the application used Php and the Bootstrap framework. The application created is divided into 3 users, namely Admin who can access the entire application menu, Head of warehouse who can input the feed management process and owner who can see the results of reports.